Kewarganegaraan dan Hak Asasi Manusia : Perspektif Hukum Nasional dan Hukum Islam - Ashfiya Nur Atqiya; Ahmad Muhamad Mustain Nasoha; Cahya Juwanti Arum Sari; Nurmi Syahidah; Rifky Azuan Syahlevi (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
The relationship between citizenship, human rights, national law, and Islamic law. Citizenship provides a formal basis for individuals in a state, while human rights are fundamental rights guaranteed by the constitution and international instruments. Islamic law also emphasizes the protection of human rights based on the principles of justice and dignity. This study compares how national law and Islamic law regulate citizenship and human rights, and seeks how both can complement each other in strengthening the protection of individual rights in Indonesia. With a normative and comparative legal approach, it is hoped that this study can contribute to creating an inclusive, just, and humanist legal system that respects diversity and moral values, and is able to handle contemporary issues such as the protection of minority groups and women's rights.